THE APPLICATION OF IСT IN THE ASSESSMENT OF EDUCATIONAL ACHIEVEMENTS IN ENGLISH OF HIGHER EDUCATION STUDENTS - Sovhar, Oksana (Journal of Information Technologies in Education (ITE), 2023)
The article analyzes the place and role of pedagogical assessment in the organization of the educational process in higher education institutions. It highlights that the objective results of assessment are an important component in the formation of a competence approach to the professional training of modern specialists. Generalized theoretical developments of domestic and foreign scientists on the given problem are considered, the analysis of which proves that pedagogical assessment has always ranked high in providing educational services. It is noted that although placement, diagnostic, progress, achievement, and proficiency tests have been the main forms of assessment in higher education institutions for quite some time, with the beginning of digitalization of educational system, objective conditions have led to implementation of pedagogical assessment using information and communication technologies. A global pandemic as well as the war in Ukraine urge the expansion of possibilities and improvement of the quality of pedagogical assessment of students’ learning outcomes using distance learning technologies. Therefore, the state and potential of educational assessment are analyzed; results of measuring learning outcomes using distance learning technologies in higher education institutions are investigated. It was found that there are adequate conditions for distance learning of students via various Language Management Systems LMS (Moodle, Brightspace, Docebo, Edmondo, Schoology) in Ukrainian institutions of higher education. At the same time, the survey taken by the educational process stakeholders confirmed the hypothesis that faculty and students are not quite ready to accept pedagogical assessment carried out through the medium of distance learning technologies which considerably complicates objective assessment and evaluation of learning outcomes in the absence of face-to-face communication. In order to meet the present day requirements, a set of measures is proposed regarding the preparation and conduct of pedagogical assessment of students’ learning outcomes using digital technologies.